Transcriptome Analysis in Brassica rapa under the Abiotic Stresses Using Brassica 24K Oligo Microarray - Lee, S.C. (National Institute of Agricultural Biotechnology, RDA, Suwon, Republic of Korea); Lim, M.H. (National Institute of Agricultural Biotechnology, RDA, Suwon, Republic of Korea); Kim, J.A. (National Institute of Agricultural Biotechnology, RDA, Suwon, Republic of Korea); Lee, S.I. (National Institute of Agricultural Biotechnology, RDA, Suwon, Republic of Korea); Kim, J.S. (National Institute of Agricultural Biotechnology, RDA, Suwon, Republic of Korea); Jin, M.A. (National Institute of Agricultural Biotechnology, RDA, Suwon, Republic of Korea); Kwon, S.J. (National Institute of Agricultural Biotechnology, RDA, Suwon, Republic of Korea); Mun, J.H. (National Institute of Agricultural Biotechnology, RDA, Suwon, Republic of Korea); Kim, Y.K. (GreenGene Biotech Inc. Genomics and Genetics Institute, Yongin, Republic of Korea); Kim, H.U. (National Institute of Agricultural Biotechnology, RDA, Suwon, Republic of Korea); Hur, Y.K. (Chungnam National University, Daejeon, Republic of Korea); Park, B.S. (National Institute of Agricultural Biotechnology, RDA, Suwon, Republic of Korea), E-mail: pbeom@rda.go.kr (Molecules and cells, 2008)
Genome wide transcription analysis in response to stresses is essential to provide the basis of effective engineering strategies to improve stress tolerance in crop plants. In order to perform transcriptome analysis in Brassica rapa, we constructed a B. rapa oligo microarray, KBGP-24K, using sequence information from approximately 24,000 unigenes and analyzed cold (4℃), salt (250 mM NaCl), and drought (air-dry) treated B. rapa plants. Among the B. rapa unigenes represented on the microarray, 417 (1.7%), 202 (0.8%), and 738 (3.1%) were identified as responsive genes that were differently expressed 5-fold or more at least once during a 48-h treatment with cold, salt, and drought, respectively. These results were confirmed by RT-PCR analysis. In the abiotic stress responsive genes identified, we found 56 transcription factor genes and 60 commonly responsive genes. It suggests that various transcriptional regulatory mechanisms and common signaling pathway are working together under the abiotic stresses in B. rapa. In conclusion, our new developed 24K oligo microarray will be a useful tool for transcriptome profiling and this work will provide valuable insight in the response to abiotic stress in B. rapa.